渐开线齿轮齿根过渡曲线最佳线型实现方法 - 董新华; 马勇; 柳强 (Jixie chuandong)
Based on finite element optimization analysis principle and using of characteristics of NURBS spline curve,through the shape optimization of standard involute gear tooth root part operated in Pro/E and ANSYS workbench software,a new realization method of involute gear tooth root transition curve best linetype is proposed.This method is practical,easy popularity and significantly improves stress condition of tooth root which is good for cutting down the broken probability of tooth root.